Plan estratégico de marketing para la Clínica Veterinaria Bassetïs, ubicada en el norte de la ciudad de Quito - Jiménez Aldaz, Diana Mariuxi (2009)
Based on this analysis it is considered that if the clinic continues its work without making a planning strategic marketing not take advantage of the opportunities offered by the good use of advertising in addition to the ~ 8 ~ creation of a new basic tool especially in the marketing area, achieved clinical position in this market, requiring a profound change in their planning, creating a change in the processes and strategies that lead to improved management of the company.